RETRACTED: Children’s Literature: A Reading of Posthumanism and the Animality - Pokhrel, Dilip (The Journal of Aadikavi, 2023)
Retraction Notice Due to a high level of plagiarism, the editors of The Journal of Aadikavi retracted this article on 4th June 2024.